EFEK TERAPI BEKAM BASAH TERHADAP SKALA NYERI DAN KUALITAS HIDUP PADA PENDERITA NYERI LEHER NON - SPESIFIK DI RUMAH BEKAM KOTA MEDAN TAHUN 2020 - DELVA ANZANI; HENDRA SUTYSNA (JURNAL ILMIAH KOHESI, 2021)
Neck pain is a musculoskeletal disorders that often occur and causing the limitations of activity in daily life. Cupping therapyis an complementary therapy and a highly developed alternative nowadays that can be used as a therapy for neck pain.This research aimed to determine the effect of cupping therapy towards the pain scale and quality of life in patients with anon-specific neck pain. This research is a comparative obeservational analytic study with a cohort study approach.The subjects in this research amounted to 13 people who were taken by the consecutive sampling method. Data analysisusing paired t-test or Wilcoxon test. Wilcoxon test showed that was a significant difference in pain scale (p=0,001).In the quality of life domains, through the Wilcoxon test were only conducted a significant difference in physical function scale(p=0,001), vitality (P=0,003), and pain (p=0,001). There was a significant effect in pain scale, but not in all the quality of lifedomains.